Current law and social problems. - Macdonald, Ronald St. J., 1928-2006 (Toronto University Press, 1961)
This is the second volume in a series which has been founded by the Faculty of Law in the University of Western Ontario as a forum for presentation of research in law and related social sciences. The primary object of the series is to promote collaboration between lawyers, social scientists, juristic philosophers, and others who are interested in exploring social values, processes, and institutions. In the present volume the Editorial Committee continues its policy of presenting papers public law and public aspects of private law, jurisprudence, and associated philosophy, constitutionalism, and juridicial international questions. The volume opens with a far-reaching comparative study of mental incapacity in criminal law by the First Lady of American criminal law. This is followed by a much needed factual discussion of law and morals. The remaining essays, apart from a short note on narcotic drug addiction, consider various aspects of current problems in international law, the study of impartiality in legal systems being especially timely in view of recent changes in the United Nations Secretariat.